The sun is a compass eaudiobook A 4,000-mile journey into the alaskan wilds. - Van Hemert, Caroline (2019)
This gripping true story follows a biologist's human-powered journey from the Pacific Northwest to the Arctic to rediscover her love of birds, nature, and adventure—perfect for fans of Cheryl Strayed.​ During graduate school, as she conducted experiments on the peculiarly misshapen beaks of chickadees, ornithologist Caroline Van Hemert began to feel stifled in the isolated, sterile environment of the lab. Worried that she was losing her passion for the scientific research she once loved, she was compelled to experience wildness again, to be guided by the sounds of birds and to follow the trails of animals. In March of 2012, she and her husband set off on a 4,000-mile wilderness journey from the Pacific rainforest to the Alaskan Arctic, traveling by rowboat, ski, foot, raft, and canoe. Together, they survived harrowing dangers while also experiencing incredible moments of joy and grace — migrating birds silhouetted against the moon, the steamy breath of caribou, and the bond that comes from sharing such experiences. A unique blend of science, adventure, and personal narrative, The Sun is a Compass explores the bounds of the physical body and the tenuousness of life in the company of the creatures who make their homes in the wildest places left in North America. Inspiring and beautifully written, this love letter to nature is a lyrical testament to the resilience of the human spirit. Winner of the 2019 Banff Mountain Book Competition: Adventure Travel